O ensino da clarineta em nível superior: materiais didáticos e o desenvolvimento técnico-interpretativo do clarinetista - Lima, Eduardo Filippe de (2019)
This paper presents and discusses the results of a research about musical instrument teaching and the use of didactic materials, more specifically on the processes involved in the teaching of clarinet in higher education. The general objective of the research was to understand the main relationships between the didactic materials most used by clarinet teachers in the Bachelor of Music courses of the Federal University of Paraíba, Federal University of Pernambuco and the Federal University of Rio Grande do Norte, and the technical and interpretative development of the clarinetist. For this, the methodological process included bibliographical and documentary research, and semi-structured interviews with clarinet teachers from the chosen institutions. In order to understand how the process of musical development happens, the theoretical basis of this work has covered the perspectives of texts of the field of musical education about the subject, having as fundamental aspect the studies around part of the theories on the musical cognitive development of Keith Swanwick, more specifically the Spiral Model of Musical Development. The main research results point out that the didactic materials most used by the clarinet teachers interviewed were mostly elaborated by nineteenth century European clarinetists, and although they were constructed in a totally empirical way, they cover the technical and interpretative aspects that the theoretical referential based on the conceptions theoretical-methodological aspects of musical education presents as necessary for the process of musical development of the instrumentalist. However, based on the data of the study, it was possible to note that even if the materials have a content oriented to specific concepts, the teacher will have a prominent role in the appropriateness of this direction proposed by the didactic material and the specificities of the student, so his development will be effective. This paper presents and discusses the results of a research about musical instrument teaching and the use of didactic materials, more specifically on the processes involved in the teaching of clarinet in higher education. The general objective of the research was to understand the main relationships between the didactic materials most used by clarinet teachers in the Bachelor of Music courses of the Federal University of Paraíba, Federal University of Pernambuco and the Federal University of Rio Grande do Norte, and the technical and interpretative development of the clarinetist. For this, the methodological process included bibliographical and documentary research, and semi-structured interviews with clarinet teachers from the chosen institutions. In order to understand how the process of musical development happens, the theoretical basis of this work has covered the perspectives of texts of the field of musical education about the subject, having as fundamental aspect the studies around part of the theories on the musical cognitive development of Keith Swanwick, more specifically the Spiral Model of Musical Development. The main research results point out that the didactic materials most used by the clarinet teachers interviewed were mostly elaborated by nineteenth century European clarinetists, and although they were constructed in a totally empirical way, they cover the technical and interpretative aspects that the theoretical referential based on the conceptions theoretical-methodological aspects of musical education presents as necessary for the process of musical development of the instrumentalist. However, based on the data of the study, it was possible to note that even if the materials have a content oriented to specific concepts, the teacher will have a prominent role in the appropriateness of this direction proposed by the didactic material and the specificities of the student, so his development will be effective.